A novel function of TLR4 in mediating the immunomodulatory effect of Benzanthrone, an environmental pollutant. (5th July 2017) - Tewari, Prachi; Mandal, Payal; Roy, Ruchi; Asthana, Somya; Dwivedi, Premendra D; Das, Mukul; Tripathi, Anurag
Graphical abstract: Highlights: Potential membrane receptor targets (TLRs) of BA. A novel function of TLR suggesting that TLRs may recognize xenobiotics. BA exposure induced inflammation via TLR 4 and its downstream signaling cascade. TLR4 inhibitor (TAK 242) significantly reduced the BA induced inflammation. Abstract: Our prior studies have reported that Benzanthrone (BA) manifests inflammatory responses in the spleen of Balb/c mice. The present investigation was carried out to study the impact of BA on macrophages, which are the primary scavenger cells in the body that act as a connecting link between innate and adaptive immunity. Parenteral administration of BA (daily for one week) to mice resulted in enhanced levels of nitric oxide (NO) and overexpression of inflammatory markers (COX-2, MMP-9 and PGE-2) in macrophages; however the level of MHC class-I and MHC class-II receptors were down regulated. Further, the potential membrane receptor targets (TLRs) of BA and its interaction with TLRs was investigated using computational methods. Professional phagocytes play pivotal roles in sensing bacteria through pathogen-associated molecular patterns (PAMPs) by various pathogen recognition receptors (PRRs), including Toll-like receptors (TLRs). Several studies have implicated these TLRs in the amplification of the inflammatory responses, however the fundamental role played by TLRs in mediating the inflammation associated with xenobiotics is still obscure and not understood. From the in silico analysis, it was evident that BA showed the highest binding affinity with TLR4 as compared to other TLRs. The western blotting studies confirmed that BA exposure indeed upregulated the expression of TLR 4, 5 and 9. Moreover, the downstream signaling cascade proteins of TLRs such as myeloid differentiation primary response protein-88 (MyD88), IL-1 receptor associated kinase (IRAK-1), and TNFR-associated factor (TRAF-6) were found to be enhanced in the BA treated groups. It was also observed that BA treatment increased the expression of ICAM-1, p-Lyn, p-Syk, p-PI3-K, IP3, PLC-γ, cAMP and Ca +2 influx, which are known to play a critical role in TLR mediated inflammation. Earlier we found that toxic effects of BA in spleen were mediated by oxidative stress which was partially neutralized by NAC exposure. Hereby, we report that NAC treatment in conjunction with BA attenuated the expression of BA induced TLR4, as well as the inflammatory markers such as COX2 and p-NFkB in macrophages. These findings demonstrated the critical role of TLRs in the regulation of the BA-induced inflammation.